Hubungan antara trait personaliti dengan tingkah laku kepimpinan - Md Nawi, Nurul Hudani; Redzuan, Ma'rof; Hamsan, Hanina Halimatusaadiah; Adam Assim, Mohd Ibrani Shahrimin (Penerbit UTM Press, 2014)
The main objective of this cross-sectional study is to determine the inter relationship of personality trait (Conscientiousness, Openness to experience, Extraversion, Agreeableness) and transformational leadership among school educator leaders in High Performance Schools (SBT). Two sets of questionnaire to measure leadership behavior and personality trait were administered to 306 (89%) (132 = male; 174 = female) and subjects who were selected by stratified random sampling in 15 SBT schools in Malaysia. Data were analyzed through inferential statistics such as correlation. The finding of the bivariate analysis using the Pearson correlation method indicates that the personality trait such as Conscientiousness (r=. 448, p<0.01), Openness to experience (r=. 605, p<0.01), Extraversion (r=.410, p<0.01), Agreeableness(r=.141,p<.05)are positively and significantly correlated with transformational leadership among the school educator leaders. However there is no correlation between Agreeableness (r=.068, p>.05) and transactional leadership.This finding clarify by possesing such positif and quality of personality trait will make educator leaders practice more transformational leadership behaviour.On implication note, having potential and capability of positive and consistent personality trait will be a benchmarik for an educator leader to play an important responsibilities in the changes environment especially in educational contexts.